(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
One of South Africa’s most successful recent branding initiatives is the rebranding and repositioningof SABMiller’s Castle Lite beer. Light beer branding has a long and successful history in the UnitedStates, where brand names like Bud Light have long held a significant market share. However,sales of Castle Lite were low, leading into 2009. SABMiller’s approach to bolster sales was tobuild a narrative around the brand that moved away from the concept of ‘light’, or ‘low calorie’,or even ‘low alcohol’ and reframe the consumer perception of this beer around the symbolicvalue of ‘Extra Cold Refreshment’. This article examines the means through which Castle Liteconsumers were invited to form a unique, imagined community of beer drinkers through a numberof media formats. It offers advertisers, academics and brand managers a concise case studythat illustrates how a failing brand can be relatively quickly repositioned to dramatically increasemarket penetration, consumer brand knowledge and overall sales.